RNA polymerase II contributes to preventing transcription-mediated replication fork stalls - Felipe-Abrio, Irene (EMBO J, 2015)
Transcription is a major contributor to genome instability. A main cause of transcription-associated instability relies on the capacity of transcription to stall replication. However, we know little of the possible role, if any, of the RNA polymerase (RNAP) in this process. Here, we analyzed 4 specific yeast RNAPII mutants that show different phenotypes of genetic instability including hyper-recombination, DNA damage sensitivity and/or a strong dependency on double-strand break repair functions for viability. Three specific alleles of the RNAPII core, rpb1-1, rpb1-S751F and rpb9Δ, cause a defect in replication fork progression, compensated for by additional origin firing, as the main action responsible for instability. The transcription elongation defects of rpb1-S751F and rpb9Δ plus our observation that rpb1-1 causes RNAPII retention on chromatin suggest that RNAPII could participate in facilitating fork progression upon a transcription-replication encounter. Our results imply that the RNAPII or ancillary factors actively help prevent transcription-associated genome instability.